Pengaruh Leverage, Ukuran, dan Profitabilitas terhadap Nilai Perusahaan dengan CSR sebagai Variabel Moderasi pada Bank di BEI 2019–2023 - Nanda Handayani Rambe; Listiorini Listiorini (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The increasingly competitive business environment compels every company to enhance its performance and formulate effective strategies to optimize firm value as a long-term objective. In this context, the banking sector holds a strategic position in supporting national economic stability, where public trust is highly dependent on the bank’s performance. This study aims to examine the influence of leverage, firm size, and profitability on firm value, with Corporate Social Responsibility (CSR) serving as a moderating variable in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The analytical methods employed include Moderated Regression Analysis (MRA) and multiple linear regression. The results indicate that leverage, firm size, and profitability have a significant effect on firm value. However, CSR does not moderate the relationship between these three variables and firm value. Despite this, the findings highlight that CSR implementation remains essential in strengthening a bank’s image and enhancing public trust, which ultimately supports the improvement of firm value amid intense competition in the banking industry.